Conventional and molecular characterization of Brucella abortus and detection of antibodies against Brucella abortus in cattle and buffaloes - PANDEY, SHALINI; CHACHRA, DEEPTI; KAUR, PUSHPINDER; CHANDRA, MUDIT; SHARMA, N S (The Indian Journal of Animal Sciences, 2014)
Brucella abortus biotype-1 (9; 5 from cattle and 4 buffaloes) were isolated from 108 samples comprising aborted foetal stomach contents, foetal membranes and uterine discharges and vaginal mucous from cattle and buffaloes. Out of the 91 serum samples tested for the presence of antibodies against B. abortus, 39 were found positive by Rose Bengal plate test (RBPT). Only 5 animals were found positive both serologically and in isolation. In all cattle and buffaloes tested for isolation 5 (8.19%) cattle and 4 (8.51%) buffaloes were found positive for B. abortus whereas serologically 32 (41.6%) cattle and 7 (50%) buffaloes were positive. In cattle and buffaloes number of positive cases was the highest (12.12% and 15.4% on isolation and 47.2% and 66.7% serologically, respectively) in 4–6 year age group.